S142 The role of H3K27 methylation in vascular endothelial cell proliferation and function: implications for pulmonary arterial hypertension. (14th November 2013) - Shao, D; Gambaryan, N; Meng, C; Perros, F; Humbert, M; Adcock, I; Wort, S
Abstract : Introduction and Objectives: There is increasing interest in the role of epigenetic gene regulation in the pathogenesis of pulmonary arterial hypertension (PAH), a condition associated with pulmonary vascular cell proliferation. Methylation on histone H3K27 (H3K27me3) has been found to be a key regulator of development and cell homeostasis. Methylation at H3K27 can be reversed by Jumonji C (JmjC) domain-containing proteins, JMJD3. We were interested to determine the immunohistochemical distribution of H3K27me3 and JMJD3 proteins in patients with IPAH and the effect of GSK-J4, an inhibitor of JMJD3, on markers of pulmonary vascular cell proliferation. Methods: Immunohistochemistry for JMJD3 and H3K27me3 was performed on human lung from normal healthy controls and patients with idiopathic PAH. The role of JMJD3 on cell cycle regulator (cyclin) expression in response to serum stimulation, with and without GSK-J4, was performed on normal human pulmonary artery endothelial cells (HPAECs) and RT-qPCR was then performed using QuantiTec primer assays. Chromatin Immunoprecipitation (CHiP) was performed antibody against H3K27me3 on normal HPAECs and analysed by quantitative PCR. Results: We found that the expression of JMJD3 protein is increased in the walls of pulmonary arteries of patients with idiopathic PAH compared to health control. This correlated to a decreased expression of H3K27me3. Treatment of HPAECs with GSK-J4, the inhibitor of JMJD3, in vitro, significantly increased cell cycle regulator p19, p27, CDK4 and CDK6 mRNA expression (Fig. 1, n = 3), whilst having no effect on p14, p16, p21 and CDK2 (data not shown). Furthermore, CHiP using a specific H3K27me3 antibody, followed by RT-qPCR analysis, demonstrated that GSK-J4 treatment increased H3K27me3 occupation on the transcription start sites of p27 and CDK4, whilst the negative control compound GSK-J5 had no effect (n = 2). Conclusion: Our data suggest that JMJD3 and H3K27 histone methylation could play an important role in cell cycle progression and cell cycle exit of pulmonary vascular cells in patients with idiopathic PAH. As such drugs such as GSK-J4 may provide a therapeutic option in the future to reverse pulmonary vascular remodelling.